Ni0.5Co0.5S nano-chains: a high-performing intercalating pseudocapacitive electrode in asymmetric supercapacitor (ASC) mode for the development of large-scale energy storage devices - Kushwaha V.; Mandal K.D.; Gupta A.; Singh P. (My University, 2025)
Grid-scale energy storage solutions are necessary for using renewable energy sources efficiently. A supercapattery (supercapacitor + battery) has recently been introduced as a new variety of hybrid devices that engage both capacitive and faradaic charge storage processes. Nano-chain architectures of Ni0.5Co0.5S electrode materials consisting of interconnected nano-spheres are rationally constructed by tailoring the surface structure. Nano-chains of the bimetallic sulfide Ni0.5Co0.5S are presented to have a superior charge storage capacity. The Ni0.5Co0.5S nano-chain electrode presents a capacitance of 2001.6 F g−1 at 1 mV s−1, with a specific capacity of 267 mA h g−1 (1920 F g−1) at 1 A g−1 in 4 M KOH aqueous electrolyte through the galvanostatic charge-discharge (GCD) method. The reason behind the high charge storage capacity of the materials is the predominant redox-mediated diffusion-controlled pseudocapacitive mechanism coupled with surface capacitance (electrosorption), as the surface (outer) and intercalative (inner) charges stored by the Ni0.5Co0.5S electrodes are close to 46.0% and 54.0%, respectively. Additionally, a Ni0.5Co0.5S//AC two electrode full cell operating in asymmetric supercapacitor cell (ASCs) mode in 4 M KOH electrolyte exhibits an impressive energy density equivalent to 257 W h kg−1 and a power density of 0.73 kW kg−1 at a current rate of 1 A g−1,. © 2024 The Royal Society of Chemistry.